Mouse Adenovirus Type 1 Early Region 1A Effects on the Blood-Brain Barrier - Nagaraja Tirumuru (American Society for Microbiology, 2016)
ABSTRACT Mouse adenovirus type 1 (MAV-1) infects endothelial cells and disrupts the blood-brain barrier (BBB), causing encephalitis in inbred and outbred mice. Using a virus mutant that does not produce the early region 1A protein E1A, we investigated whether the activity of this known viral transcriptional regulator is needed for BBB disruption and other phenotypes associated with encephalitis. The wild-type (wt) virus and E1A mutant virus caused similar levels of permeability of sodium fluorescein in brains of infected mice. In an in vitro assay of BBB integrity, wt and mutant virus caused similar decreases in transendothelial electrical resistance in primary mouse brain endothelial cell monolayers. These results indicate that E1A protein does not contribute to disruption of BBB integrity in animals or cultured cells. Both wt and E1A mutant virus infection of mice led to similar increases in the activity of two matrix metalloproteinases known to correlate with BBB disruption, MMP2 and MMP9, while causing no increase in the steady-state expression of MMP2 or MMP9 mRNA. In contrast, the amount of MMP3 transcripts increased upon infection by both viruses and to a higher level in infections by the mutant virus lacking E1A protein production. There was no difference in the levels of steady-state expression of mRNA for tight junction proteins among mock virus, wt virus, and mutant virus infections. Thus, the MAV-1 E1A protein does not measurably affect BBB integrity in the parameters assayed, although it reduces the amount of MMP3 mRNA steady-state expression induced in brains upon infection. IMPORTANCE Encephalitis can be caused by viruses, and it is potentially life-threatening because of the vital nature of the brain and the lack of treatment options. MAV-1 produces viral encephalitis in its natural host, providing a model for investigating factors involved in development of encephalitis. MAV-1 infection disrupts the BBB and increases activity of matrix metalloproteinases in brains of infected mice. We investigated whether the major transcriptional regulator of adenoviruses, E1A protein, is responsible for any of the specific phenotypes that result from MAV-1 infection. For some of the functions assayed, an E1A mutant virus behaved like wild-type virus. However, expression of mRNA for one matrix metalloproteinase was higher in the virus lacking E1A protein production. This highlights the complex nature of encephalitis and suggests that E1A may have transcriptional effects on host genes important for the development of encephalitis.